Effects of Atriplex halimus and Ajuga iva L. Schreb on Calcium Oxalate Urolithiasis Risk in vitro - Beghalia, M.; Ghalem, S.; Allalia, H.; Belouatek, A.; Marouf, A. (Asian Journal of Chemistry, 2010)
In this work, an in vitro crystallization study enabling the specification of kinetic and thermodynamic conditions for the formation and growth of crystalline calcium oxalate has been performed. Some medicinal plants were used as inhibitors, thus preventing, slowing down or reducing crystallization phases. A classical model was chosen for the study of oxalate crystallization because of its simplicity and satisfying reproducibility. This model involves the crystallization study with and without inhibitor, in order to assess the inhibition capacity of any used chemical specie. Two solutions of dihydrated calcium chloride (40 mM/L) and sodium oxalate (4 mM/L) are prepared in presence of an amount sufficient enough of sodium chlorite. The oxalate crystal development was monitored by polarization microscopy at different time intervals. Thus, in the absence of inhibitor, crystallization of calcium oxalate led to the formation of a calcium oxalate crystal after 0.5 h. In presence of inhibitors at lower concentrations however, inhibition was partial. The addition of Atriplex halimus L. or Ajuga iva (L.) Schreber acted on the phase of growth crystallization. The rates of inhibition capacity at a 75 % concentration of Atriplex halimus and Ajuga iva were 97.82 and 97.01 %, respectively. These inhibitors developed an important inhibition capability at low concentrations. Calcium oxalate monohydrate compounds encountered in urine could be dangerous and thus using inhibitors to prevent, slow down or reduce crystallization phases might be very helpful. In this study, Atriplex halimus and Ajuga iva are shown to be good inhibitors.